2019
DOI: 10.3390/nano9050672
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Novel SERS Platform Based on Mantis Wing with High-Density and Multi-Level “Hot Spots”

Abstract: The recent development of SERS substrates based on irregular nanostructures for directly molecule recognition has aroused increasing attention. By combining the irregular flake-like nanostructures of mantis wings, high SERS performance of Ag nanofilms, and the chemical stability of Au nanoparticles (NPs), an ultra-sensitive and flexible SERS substrate based on Au NPs functionalized Ag nanofilms-mantis wings (Au-Ag-M.w.) hybrid system is successfully fabricated. When 4-aminothiophenol is selected as the probe m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It is generally accepted that the RSD of less than 20% for the variation in the Raman signal intensity is an indicator for a SERS substrate with good uniformity or reproducibility. 27 In this study the characteristic band of the DFC at 808 cm À1 was selected to examine the variation of the Raman signal intensity. Calculations showed that for 15 random spots on the same AgNPs substrate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that the RSD of less than 20% for the variation in the Raman signal intensity is an indicator for a SERS substrate with good uniformity or reproducibility. 27 In this study the characteristic band of the DFC at 808 cm À1 was selected to examine the variation of the Raman signal intensity. Calculations showed that for 15 random spots on the same AgNPs substrate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ag nanoparticles (AgNPs) were used as an SERS substrate and were observed with enhanced Raman signal for rapid detection of difenoconazole in grapes [15] Besides, numerous scientific studies have recently shown that some natural materials display unique surface superhydrophobicity owing to their hierarchical micro nanostructures, thus showing potential in low-cost SERS applications [16]. Biomaterials from rose petal [17,18], taro leaf [19], mantis wings [20], or butterfly wings [21] were easily treated with noble metals that exhibited outstanding SERS effects for multiple-molecule simultaneous identification with a very low limit of detection (LOD) (10 −8 -10 −10 mg/mL). However, using natural materials, such as rose petals, has been observed with great difficulties due to its short storage time, leading to a lack of initiative for SERS application.…”
Section: Introductionmentioning
confidence: 99%